Co‐design with aboriginal and torres strait islander communities: A journey. (29th August 2022) - Tamwoy, Nathaniel; Rosas, Sylvia; Davis, Scott; Farthing, Annie; Houghton, Caitlin; Johnston, Hannah; Maloney, Catherine; Samulkiewicz, Nicole; Seaton, Jack; Tuxworth, Gemma; Bat, Melodie
Abstract: Aim: This paper explores the principles of co‐design with Aboriginal and Torres Strait Islander communities by reflecting on the literature, learning from experiences of allied health professionals, and considering how co‐design can be applied in rural and remote allied health practice. Context: This paper has been authored by a working group from Services for Rural and Remote Allied Health (SARRAH). SARRAH is a member‐based allied health organisation, working to improve health outcomes for rural and remote Australians. SARRAH has been representing and supporting allied health professionals in rural and remote Australia for over 20 years, with a member base that includes students, practitioners, programme managers, policy makers and academics. As a non‐Indigenous organisation, SARRAH works in partnership and receives guidance from the peak organisation, Indigenous Allied Health Australia (IAHA). Approach: Over a period of 3 months, a group of eleven SARRAH members and staff came together to review available literature, seek member perspectives and share their experiences and understandings of co‐design. Working group discussions were grounded in the knowledge and experiences shared by two Aboriginal and Torres Strait Islander group members. Conclusion: This paper proposes that successful co‐design with Aboriginal and Torres Strait Islander communities places legitimate value on different knowledge systems, is built on strong and trusting relationships, promotes inclusive involvement and requires authentic partnerships. Using these principles, SARRAH will engage with members and stakeholders to influence meaningful change in allied health practice in rural and remote Australia.